Sensorer och system i mjölkkobesättningar - Kinander, Karin (2010)
The trend in milk production is similar in Sweden and across the world; the farms are getting fewer but increasingly bigger. The costs for hiring workers are increasing, which results in more cows per animal keeper. Sensors can then be a great tool for keeping track of animals which need special attention. With a reported decreasing fertility, sensors that can detect oestrus even at low levels can be especially helpful in bigger herds to pinpoint the cows that may be in oestrus. The number of farms with dairy cows that install AMS, Automatic Milking Systems, are increasing, and that also increases the need for sensors to control milk quality and composition when there is no visual control of the milk by a milker before milking starts.